Implementasi Model Pembelajaran Sentra Di Kelompok Bermain Taman Pendidikan Prasekolah (TPP)Al Firdaus Kota Surakarta Tahun Pelajaran 2015 / 2016 - Hakim, Intan Nurwiyati (2016)
The purpose of this study is to investigate the implementation of the model of learning centers in Park Preschool Playgroup (TPP) Al Firdaus. This research is a qualitative descriptive study. Data collection techniques in this study using observation and interviews. Analysis of the data in this study using the analysis model of Miles and Huberman, is to perform data reduction (data reduction), a data display (presentation of data), and conclusion drawing. The results of the research center of the beam learning implementation in preschool (TPP) Al Firdaus is good enough. Stepping before playing the rules of the game and the game has not been given a choice. Scaffolding when playing physical intervention, the question is divergent, motivation, non direct teaching, and direct statement (directive statement) has not been granted. Scaffolding after playing some of the teachers do not give recalling. Teachers not made a judgment that is connected to the main stage of the beam.